PENERAPAN STRATEGI PEMBELAJARAN THINK-TALK-WRITE UNTUK MENINGKATKAN KEMAMPUAN DISKUSI PADA POKOK BAHASAN EVOLUSI - Aynin Mashfufah; Candra Utama (JURNAL PENA SAINS, 2016)
The study of the Biology through learning strategy of Think-Talk-Write (TTW) has been implemented and tested on 30 students of XII Science-1 SMAN 1 Tanggul using one-group pretest-posttest design. The purpose of this study is developing discussion skill and learning outcomes of students. Data were analyzed by descriptive and qualitative, the results are as follows: well performed learning, the student’s learning outcome is increase, good discussion skills and most students give good response to Think-Talk-Write strategy. The conclusions of this study is that Think-Talk-Write strategy can increase discussion skill and learning outcome.